2010
DOI: 10.1002/ange.201001110
|View full text |Cite
|
Sign up to set email alerts
|

Magnetische Suszeptibilitätsmessung und 57Fe‐Mößbauer‐ Spektroskopie an einem ferromagnetischen FeIII4Dy4‐Ring

Abstract: In memoriam Ian J. HewittBei der Suche nach kleineren und effektiveren magnetischen Materialien hat sich die Aufmerksamkeit in letzter Zeit auf Fe III -4f-Heterometallkomplexe gerichtet. Diese Komplexe kombinieren paramagnetische High-spin-Fe III -Ionen mit stark anisotropen 4f-Ionen, und einige dieser Komplexe sind Einzelmolekülmagnete (SMMs).[1] In den meisten der bisher beschriebenen SMMs ist die dominierende magnetische Wechselwirkung von antiferromagnetischer Natur, aber es besteht wenig Zweifel daran, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 8 publications
(4 reference statements)
0
5
0
2
Order By: Relevance
“…Heterometallic complexes containing 3d and 4f block paramagnetic ions have been extensively considered since the revolutionary investigation by Gatteschi et al on the Cu II /Gd III based complexes which bestowed a whim to the advancement of 3d–4f associated chemistry . Until now, numerous 3d‐4f heterometallic molecular magnetic assembly with diverse structures and topologies of paramagnetic centres have been revealed based on cobalt(II), copper(II), chromium(III), manganese (II/III),, iron(II/III) ion. The appraisal of literature study revealed that ferromagnetic coupling, that is favourable for slaking of the QTM phenomena and improving energy barriers, amongst Cu II /Ln III[27,28] and Ni II /Ln III[29–34] ions indicate an advantageous combination to assemble 3d–4f heterometallic complexes with novel topologies for SMM study.…”
Section: Introductionmentioning
confidence: 99%
“…Heterometallic complexes containing 3d and 4f block paramagnetic ions have been extensively considered since the revolutionary investigation by Gatteschi et al on the Cu II /Gd III based complexes which bestowed a whim to the advancement of 3d–4f associated chemistry . Until now, numerous 3d‐4f heterometallic molecular magnetic assembly with diverse structures and topologies of paramagnetic centres have been revealed based on cobalt(II), copper(II), chromium(III), manganese (II/III),, iron(II/III) ion. The appraisal of literature study revealed that ferromagnetic coupling, that is favourable for slaking of the QTM phenomena and improving energy barriers, amongst Cu II /Ln III[27,28] and Ni II /Ln III[29–34] ions indicate an advantageous combination to assemble 3d–4f heterometallic complexes with novel topologies for SMM study.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the SMM behavior, hysteresis loops were recorded using a micro‐Hall magnetometer for which a sufficient range of sweep rates is available11 on a crystal well coated in Apiezon grease. Even if such a crystal fractures on cooling the grease prevents any movement of the fragments and the measurements correspond to those on aligned single crystallites.…”
Section: Energy (Cm−1) Of the Lowest Kramers Doublets On Individual Mmentioning
confidence: 99%
“… The cores of Fe‐Ln compounds discussed herein: Fe 3 Ln (top),6a Fe 4 Ln 4 (middle),6b and Fe 2 Ln 2 (bottom) 5…”
mentioning
confidence: 99%
“…Other examples analyzed herein are two octanuclear complexes [Fe III 4 (Tb/Dy) 4 (teaH) 8 (N 3 ) 8 (H 2 O)] (teaH=triethanolamine), denoted Fe 4 Ln 4 6b. The structure of these two isostructural compounds is based on a ring‐like {Fe 4 Ln 4 } 24+ core with alternating Fe III and Ln III centers.…”
mentioning
confidence: 99%